Answer:
9. a = -7
10. x = 1
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define equation
a + 6a - 14 = 3a + 6a
Step 2: Solve for a
- Combine like terms: 7a - 14 = 9a
- Subtract 7a on both sides: -14 = 2a
- Divide 2 on both sides: -7 = a
- Rewrite: a = -7
Step 3: Check
Plug in a into the original equation to verify it's a solution.
- Substitute in a: -7 + 6(-7) - 14 = 3(-7) + 6(-7)
- Multiply: -7 - 42 - 14 = -21 - 42
- Subtract: -49 - 14 = -63
- Subtract: -63 = -63
Here we see that -63 is equal to -63.
∴ a = -7 is a solution of the equation.
Step 4: Define equation
-12 - 4x = 8x + 4(1 - 7x)
Step 5: Solve for x
- Distribute 4: -12 - 4x = 8x + 4 - 28x
- Combine like terms: -12 - 4x = -20x + 4
- Add 20x on both sides: -12 + 16x = 4
- Add 12 on both sides: 16x = 16
- Divide 16 on both sides: x = 1
Step 6: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: -12 - 4(1) = 8(1) + 4(1 - 7(1))
- Multiply: -12 - 4 = 8 + 4(1 - 7)
- Subtract: -16 = 8 + 4(-6)
- Multiply: -16 = 8 - 24
- Subtract: -16 = -16
Here we see that -16 does indeed equal -16.
∴ x = 1 is a solution of the equation.